The Trends of Stream of Consciousness in William Faulkner's The Sound and The Fury - Ibrahim, Musaab Natiq; Hasan, Wasan Ali (International Journal of Psychosocial Rehabilitation, 2020)
The paper explores William Faulkner's stream of consciousness technique for his novel The Sound nd the Fury (1929) which is among the best novels in the American literature and the period of the 20th century. His best works, and his finest writing features from 1929 to 1936, the years of the difficult moments of the Great Depression in America, where the economy collapsed and resurrected shortly thereafter. The paper deals with the origin of Stream of Consciousness with different examples of certain novels, and how Faulkner succeeds to apply this literary term in his novels; by playing with some events and time especially past and present.